Longitudinal analysis of antibody profiles against plakins in severe drug eruptions: emphasis on correlation with tissue damage in drug‐induced hypersensitivity syndrome and drug reaction with eosinophilia and systemic symptoms. (28th August 2016) - Takehara, A.; Aoyama, Y.; Kurosawa, M.; Shirafuji, Y.; Umemura, H.; Kamiya, K.; Ushigome, Y.; Kano, Y.; Shiohara, T.; Iwatsuki, K.
Summary: Background: The evidence for severe drug eruption as a trigger for autoimmune disease has recently increased. No information is available on how tissue damage in severe drug eruptions can induce autoimmune responses. Objectives: To investigate whether the generation of autoantibodies (autoAbs) against plakin family proteins could be the cause or result of tissue damage in patients with severe drug eruptions and whether the generation of autoAbs could be prevented by systemic corticosteroids during the acute stage. Methods: We retrospectively analysed alterations of serum levels of autoAbs against plakin family proteins in patients with Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) and drug‐induced hypersensitivity syndrome (DiHS)/drug reaction with eosinophilia and systemic symptoms (DRESS) during the acute stage and long after resolution over a period of more than 10 years. Results: AutoAbs against plakin family proteins were detected in patients with either SJS/TEN or DiHS/DRESS regardless of the epidermal damage in the acute stage, and were sustained even long after resolution in DiHS/DRESS, indicating that those autoAbs are neither the cause nor the consequence of epidermal damage, at least in DiHS/DRESS. Severe liver damage and noncorticosteroid therapy during the early and acute stages of DiHS/DRESS were associated with the subsequent generation of these autoAbs. Conclusions: These autoAbs are neither necessarily the cause nor the result of epidermal damage in DiHS/DRESS, because the presence of these autoAbs was not restricted to patients with SJS/TEN but was also observed in those with DiHS/DRESS, which is characterized by lack of epidermal damage. Severe liver damage and/or immune responses that could be prevented by corticosteroids in the acute stage of DiHS/DRESS are among the causal factors contributing to the generation of autoimmune responses. Abstract : What's already known about this topic? Evidence for severe drug eruption as a trigger for autoimmune diseases has increased. Sera from patients with Stevens–Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) have been shown to contain autoantibodies (autoAbs) against epidermal proteins generated as a consequence of epidermal damage. No information is available about the existence of these autoAbs in drug‐induced hypersensitivity syndrome (DiHS)/drug reaction with eosinophilia and systemic symptoms (DRESS), characterized by lack of epidermal damage and gradual loss of regulatory T‐cell function. What does this study add? These autoAbs were more persistently and frequently detected in patients with DiHS/DRESS than in SJS/TEN. In DiHS/DRESS, liver damage during the early and acute phases, together with a regulatory T‐cell dysfunction, would serve to generate autoAbs. What is the translational message? Patients with severe drug eruptions benefit from corticosteroid therapy during the acute stage with regard to the subsequent development of autoimmune responses. Achievement of early resolution by corticosteroids is associated with a lower risk of subsequently developing autoimmune responses, particularly in patients with DiHS/DRESS. The need to relieve clinical symptoms by corticosteroids should be balanced with antimicrobial therapies aiming at reducing the risk of infectious diseases. Linked Comment: Chu. Br J Dermatol 2016;175 :866–867 .